(untitled) (The Review of Diabetic Studies, 2024)
Introduction: HAIs have played a major role in patient and care safety issues. Infection prevention and control (IPC) is a duty, which entails the alignment of the clinical, laboratory, nursing, pharmacy, and administrative divisions. Purpose of the Work: The objective of the work was to investigate the impact of multidisciplinary collaboration in regard to the minimization of HAIs, enhancement of patient safety, or the clinical effectiveness. Methods: The literature search occurred in the form of a systematic literature review that consisted of PubMed, Scopus, CINAHL, and Google Scholar and was conducted within the past fifteen years. The keywords which were applied in the qualitative as well as quantitative research involved multidisciplinary collaboration, infection prevention and hospital-acquired infections. Thematic analysis was applied to identify some key patterns, challenges and success factors in the collaborative IPC practices. Findings: Multidisciplinary collaboration contributes to a major decrease in HAIs, improved clinical decision-making process, as well as communication and an effect on patient satisfaction and safety. IPC can be improved through the use of products of technology, frequent training and institutional reinforcement. Recommendation: IPVs should collaborate in multidisciplinary teams to facilitate effective IPC, safer healthcare environments, better patient outcomes and sustainable practices of infection control.